Pelatihan Penganggaran Penjualan : Studi Kasus Pada Toko Oleh-Oleh Khas Mandar Di Desa Batulaya - Nurman Nurman; Anwar Anwar; Chalid Imran Musa; Burhanuddin Burhanuddin (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Planning a business can be used as a basis for making decisions that will be taken for the future. With this planning, MSMEs can identify various risks that will arise so that their business can improve its operational performance. The aim of this service is to determine sales and income projections for MSMEs in Batulaya Village. The results of the service concluded that if there is a plan, the company can ensure the continuity of the company for the long term. Apart from good planning, a company also needs to prepare a budget, so that the activities the company will carry out can be planned properly. The company budget plays a very important role in planning all company activities for a certain period of time in the future. A sales budget can provide an overview of estimates or predictions about the number of products or services that will be sold in a certain time period in the future.